Efficiency of applying "Robo Diy" technology in evolving the preschoolers’ cognitive interests (Journal of Educational Sciences, 2024)
In respect with the modernizing of contemporary education content, advancing the cognitive interests and curiosity, independence, and creating the critical thinking of preschoolers is one of the pressing issues in preschool education field. Present-day children live in the world in which information and communication technologies are speedily growing. Preschool organizations’ goal is to educate children from preschool age to be able to work with the given new technologies. Alongside, to develop children's cognitive interest in science and technology.The given article considers the application pecularities of "Robo DIY" technology in  developing the preschoolers’ cognitive interest. Analyzing the scientific research, "Robo DIY" concept’s definition has been given. There were carried out diagnostics aimed at determining the level of cognitive interest, the level of design and skills of independent activity of senior preschool age kids. Study results have been provided as well as growth efficacy of children's cognitive interest due to the new innovative approach in design has been demonstrated. It is pointed out that technology contributes not just to advancing the children's cognitive interests, but also to forming the independent thinking, expanding the knowledge, consolidating the skills, mastering the skills, and educating the moral qualities. The authors substantiate the impact of "Robo DIY" technology on augmentation of key competencies in demand in the current information society.Key words: cognitive interest, constructive game, engineering thinking, robotics, "Robo DIY", STEM education.